Strain Conditions Indicated by Metamorphic Spots in the Igarra Schist Belt, Southwestern Nigeria - Efosa Udinmwen; M. I. Oden; E. E. Ukwang; E. O. Ibegbulam (Archives of Current Research International, 2017)
Strain has been analyzed from the metamorphic spots within deformed schist and phyllite in the Igarra schist belt, southwestern Nigeria. Strain magnitudes were obtained by using the graph of length against width of spots, Harmonic mean (H), and the Rf/ø technique. The values of strain range from 1.95 – 2.99. The standard deviation of 0.4419 shows that the mean value of Rf is reliable. The direction of maximum elongation (λ1) during the deformation is approximately parallel to the NW – SE direction. The difference between the direction of maximum elongation of the spots (NW – SE) and that of the phenocryst in granite (N – S) shows that there was a change of the maximum elongation (λ1) axis during progressive deformation in this area which could be either as a result of a change in the regional tectonic axis of deformation or could be provoked by intrusion already having magmatic fabric at an angle to regional deformation. Thus, it is safe to suggest that during progressive deformation, there was either a rapid transition from the older NW – SE λ1 direction in the schist/phyllite to the younger N – S λ1 direction in The granite or the granite plutons crystalized at a remarkable slow rate to allow for a gradual transition of the maximum elongation axis. This work aims to discuss the deformation condition in the study area using metamorphic spots and buttress the deformation heterogeneity in the Igarra schist belt.